Chrononutrition Behavior During the COVID-19 Pandemic and its Relationship with Body Weight Among College Students - Norsham Juliana; Nur Islami Mohd Fahmi Teng; Khairunnisa Fazira Hairudin; Wan Asma Wan Abdul Fatah; Srijit Das (Frontiers Media S.A., 2024)
Indexed by WOS/Scopus/ERA